Ionizing radiation response of bismuth titanate-based metal-ferroelectric-semiconductor (MFS) type capacitor. (June 2022) - Kaymaz, Ahmet
Abstract: In this study, the ionizing radiation (gamma-irradiation) response of the metal-ferroelectric-semiconductor (MFS) type capacitors whose interfacial layer is bismuth titanate (Bi4 Ti3 O12 ), which is from the Aurivillius family, was investigated. The capacitance-voltage ( CV ) and conductance-voltage ( G / ω-V ) characteristics and the device parameters derived from these characteristics provide essential information about the radiation response. Therefore, MFS-type capacitors in which their Schottky/rectifier contacts Au and interfacial layer Bi4 Ti3 O12 (BTO) were prepared and exposed to various doses of gamma-rays. The voltage-dependent C and G / ω data were obtained before irradiation and after some irradiation doses using the Hewlett Packard Impedance Analyzer. Experimental results showed that the CV curves exhibited multilayer capacitor behavior before and after radiation rather than conventional Schottky structures due to the very thin Silicon dioxide (SiO2 ) interlayer at the BTO/Si interface, which was assumed to form during the annealing of BTO films in air ambient. On the other hand, the C-G / ω-V curves exhibited asymmetric and hysteretic behavior because of the different electrical properties at the bottom and top interfaces and the natural ferroelectric behavior of the BTO. On the other hand, considering the radiation effects, the C-G/ω-V characteristics and other device parameters did not show any significant changes at the 5 kGy irradiation dose, but significant differences were observed in all parameters at the 22 kGy dose. Therefore, it can be concluded that these MFS-type structures with the BTO interlayer can be used as a capacitor or radiation sensor at doses around 5 kGy and below 22 kGy. However, it is not recommended to use them as capacitors at doses close to 22 kGy due to the large capacitive change (approximately tenfold decrease) at this dose. Besides, the tendency of the device to deteriorate at 22 kGy doses indicates that it is not suitable for use as a capacitor or radiation sensor above 22 kGy gamma-irradiation doses. Highlights: In this study, the bismuth titanate-based metal-ferroelectric-semiconductor (MFS) type capacitor was produced and the effects of gamma-irradiation on the device were investigated. The device exhibited multilayer capacitor behavior before and after irradiation due to the naturally occurring SiO2 interlayer at Si/BTO interface. The device showed a tendency to deteriorate at 22 kGy ionizing radiation doses, but no significant change was observed in device parameters at 5 kGy doses. This MFS-type structure can be used as a capacitor or radiation sensor at doses around 5 kGy and below 22 kGy. It is not recommended to use this device in ionizing radiation environments at doses above 22 kGy.